DIGITAL MARKETING KEWIRAUSAHAAN LEMBAGA DAKWAH DI ERA DISRUPTIF (Studi Pada Lembaga Dewan Masjid Indonesia) - Dova, Muhammad Khalil; Castrawijaya, Cecep (Jurnal Al-Hikmah: Jurnal Dakwah, 2024)
The mosque is not just a place of worship for all Muslims, but the mosque has a function as a centre or centre of community activities. That way all activities that have positive elements can be carried out at the Mosque. One of those positive activities is entrepreneurship. The rapid development of technology and digitalisation in this disruptive era brings major changes to entrepreneurial activities, where with the rapid development of digital buying and selling activities not only occur directly but can be through mobile phones. Dawah organisations must now face new challenges by innovating their dawah approach and developing their entrepreneurial marketing digitally to support their operational sustainability. This article aims to explore how da'wah institutions, here the author takes the Indonesian Council of Mosques (DMI), can utilise digital developments as a means of marketing entrepreneurial activities in this disruptive era. This research uses qualitative methods through literature studies. Researchers used library data sources to collect data and information on the topic of entrepreneurship and Islamic preaching. The data sources collected included books, articles, and various journals related to the topic. The results showed that DMI has used digital marketing in its entrepreneurship in order to continue to exist in this disruptive era.Keywords: Digital, Entrepreneurship, Indonesian Mosque Council, Disruptive EraMasjid bukan hanya sekedar tempat untuk ibadah bagi seluruh umat Muslim, namun Masjid memiliki fungsi sebagai pusat atau sentral kegiatan umat. Dengan begitu semua kegiatan yang memiliki unsur positif dapat dilakukan di Masjid. Salah satu kegiatan positif itu adalah kewirausahaan. Perkembangan teknologi dan digitalisasi yang pesat di era disruptif ini membawa perubahan besar pada kegiatan kewirausahaan, dimana dengan pesatnya pekembangan digital kegiatan jual beli tidak hanya terjadi secara langsung tetapi bisa melalui mobile phone. Lembaga dakwah kini harus menghadapi tantangan baru dengan berinovasi dalam pendekatan dakwah dan mengembangkan pemasaran kewirausahaannya secara digital untuk mendukung keberlanjutan operasional mereka. Artikel ini bertujuan untuk mengeksplorasi bagaimana lembaga dakwah yang disini penulis mengambil Dewan Masjid Indonesia (DMI) dapat memanfaatkan perkembangan digital sebagai sarana untuk melakukan pemasaran atau marketing pada kegiatan kewirausahaan di era disruptif ini. Penelitian ini menggunakan metode kualitatif melalui studi literatur. Peneliti menggunakan sumber data perpustakaan untuk mengumpulkan data dan informasi tentang topik kewirausahaan dan dakwah Islam. Sumber data yang dikumpulkan termasuk buku, artikel, dan berbagai jurnal yang berkaitan dengan topik tersebut. Hasil penelitian menunjukkan bahwa DMI sudah menggunakan digital marketing pada kewirausahaannya agar bisa tetap eksis di era disruptif ini. Kata Kunci: Digital, Kewirausahaan, Dewan Masjid Indonesia, Era Disruptif